Выбор и использование математических методов для определения технологических параметров радиационно-защитных материалов - Моргунов, Владимир Викторович; Трищ, Роман Михайлович; Диденко, Наталья Викторовна (НТУ "ХПИ", 2016)
В статье обоснован выбор программного комплекса для проведения численного моделирования прохождения ионизирующего излучения через вещество, приведено обоснование выбора корректного метода расчета дозы и мощности дозы при проведение численного моделирования прохождения ионизирующего излучения через вещество. Предложена методика подбора аппроксимирующей кусочно-непрерывной функции для расчета массового коэффициента ослабления гамма-излучения, необходимого при расчете поглощенной и эквивалентной доз.

Ionization radiation is everywhere: cosmic rays, nuclear energy, medicine and etc. One of the main tasks during work with the ionization radiation – human safety. There are a lot of radiation protected clothes. To define their protective characteristics two way are possible: experimental and simulation. The numerical simulation allows to speed up experiments and cheapen them.There are a lot of software toolkit for ionization radiation pass through the matter simulation. The article is devoted to following tasks: selection of software toolkit for numerical simulation of ionization irradiation passage through the matter; correct way of dose and dose ray calculation as dose rate should be calculated at the point; correct way of mass energy-absorption coefficient approximation by piecwise continuous function. For numerical simulation GEANT4 software toolkit was chosen. The GEANT4 is written in modern programming language: C++. GEANT4 is well documented, has a good supprot and free open software. To calculate dose and dose rate calculation should be made for the point. The absorbed dose calculaation method which is used in GEANT4 can not be used for dose rate calculation. Proper mathematical method for absorbed dose calculation was chosen and was described in the article
Choice and use of mathematical methods to determine the technological parameters of radiation-shielding materials
Keywords: ионизирующее излучение; численное моделирование; поглощенная доза; мощность дозы; эквивалентная доза; ionization radiation; numerical simulation; dose rate